Effects of melatonin in polycystic ovary syndrome: is there Hippo pathway crosstalk? - Lijun Wang; Yuanyuan Jin; Yuanyuan Zhi; Zhenzhen Li; Meili Wang; Boda Wang; Xinbo Wang (Journal of Ovarian Research)
Abstract Objective Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder among reproductive women, characterized by hyperandrogenism, oligo-ovulation and polycystic ovarian morphology. Incorporating complementary medicine alongside traditional lifestyle therapies for PCOS may offer additional benefits for affected women. Melatonin (MT), a hormone secreted by the pineal gland, has emerged as a potential treatment for regulating ovarian function in PCOS. However, the specific effects and underlying mechanisms of MT on PCOS need to be elucidated. Methods This review consolidates evidence from randomized controlled trials, original research articles, systematic reviews, and meta-analyses regarding MT supplementation in PCOS, with a particular focus on its interaction with the Hippo pathway, to provide a comprehensive overview of current knowledge. Results Current evidence suggests that MT plays a role in modulating PCOS through various mechanisms and is associated with the Hippo pathway. However, several uncertainties and key limitations in the existing literature must be addressed before these treatments can be integrated into standard clinical practice. Clinical trial number Not applicable.